Animation or leaflet: Does it make a difference when educating young people about genome sequencing?. Issue 10 (October 2021) - Hammond, Jennifer; Garner, Ian; Hill, Melissa; Patch, Christine; Hunter, Amy; Searle, Beverly; Sanderson, Saskia C.; Lewis, Celine
Highlights: Animations and leaflets can effectively deliver genomic education to young people. Young people may engage more with genomic education in an animation format. Satisfaction appears to be higher when information is delivered as an animation. Abstract: Objective: To compare the effectiveness of an animation against two leaflets with and without images, in educating young people about genome sequencing (GS). Methods: An experimental survey with three assessment points (pre- intervention [T1], post – intervention [T2], 6-week follow-up [T3]). Participants (N = 606) were randomly assigned to receive one of three educational interventions; animation (n = 212); leaflet with images (n = 197); or leaflet with text only (n = 197). Measures of objective and subjective knowledge were completed at T1 (N = 606), T2 (N = 606) and T3 (N = 459). Measures of attitudes, intentions and beliefs towards GS and satisfaction with intervention were completed at T2 only. Results: The type of educational intervention young people received had no significant impact on their objective or subjective knowledge at both T2 and T3 (all p > .05), nor did the educational intervention type affect their attitudes, intentions and beliefs towards GS at T2 (p > .05). However, participant satisfaction was significantly higher in the animation group than the leaflet groups (p < .001). Conclusion: Animations and leaflets are both effective ways to deliver genomic education to young people, but the animations lead to higher satisfaction. Practice implications: Different individuals may find different modes of educational resources more accessible than others. Therefore a range of resources should ideally be made available to patients.